Educational tool on oncotic cytology in Primary Care (Research, Society and Development, 2022)
Objective: to develop an educational tool on oncotic cytology in primary health care. Method: this is a methodological study for the development of an educational tool with a quanti-qualitative approach, using the Content Validity Index and Cronbach's Alpha. Results: In the Delphi I round, regarding clarity, ten questions did not obtain a minimum score of 0.80 and regarding relevance, only four were approved. In the Delphi II step, all items were approved. As for Cronbach's Alpha, there was statistical significance in the Delphi I round (p≤0.05). In the Delphi II round, although the result was not statistically significant in the two criteria, the modifications made and the exclusions of the items allowed the index to be raised in both conditions. Conclusion: The summary of official protocols, followed by their compilation in the form of an educational brochure contributes to the easy dissemination of knowledge about oncotic cytology collection techniques.